Prognostic value of TIGIT in East Asian patients with solid cancers: A systematic review, meta-analysis and pancancer analysis - Li, Sicong; Li, Lanxing; Pan, Tianyan; Li, Xiaoqun; Tong, Yujia; Jin, Yongdong (Frontiers in Immunology, 2022)
Background T-cell immunoreceptor with Ig and ITIM domains (TIGIT) participates in tumor immune escape by delivering inhibitory signals to T cells. The purpose of this article was to assess the prognostic value of TIGIT and its immunological function in solid cancers. Methods Three databases were searched for relevant articles. The main endpoints were overall survival (OS), progression-free survival (PFS), recurrence-free survival (RFS), and disease-free survival (DFS). Hazard ratios (HR) were pooled by using fixed-effects or random-effects models. Pancancer analysis of TIGIT was performed based on public online databases, mainly The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), and UCSC Xena. The possible relationships between TIGIT expression and the tumor microenvironment (TME), infiltration of immune cells, immune-related genes, tumor mutation burden (TMB), and microsatellite instability (MSI) were revealed in this article. Results Sixteen studies met the inclusion criteria. High expression of TIGIT was associated with worse OS [HR= 1.73, 95% confidence interval (CI) 1.50, 1.99], PFS (HR = 1.53, 95% CI [1.25, 1.88]), RFS (HR = 2.40, 95% CI [1.97, 2.93]), and DFS (HR= 6.57, 95% CI [0.73, 59.16]) in East Asian patients with solid cancers. TIGIT expression was positively correlated with immune infiltration scores and infiltration of CD8 T lymphocytes in all of the cancers included. TIGIT was found to be coexpressed with the genes encoding immunostimulators, immunoinhibitors, chemokines, chemokine receptors, and major histocompatibility complex (MHC), especially in gastroesophageal cancer. TMB and MSI were also associated with TIGIT upregulation in diverse kinds of cancers. Conclusion High expression of TIGIT is associated with poorer prognosis in East Asian patients with solid cancers. TIGIT is a novel prognostic biomarker and immunotherapeutic target for various solid cancers because of its activity in cancer immunity and tumorigenesis.